Halal Awareness as a Boundary Condition in Halal Consumer Behavior: Evidence from Gen Z in Indonesia and Malaysia - Budi Prakoso; Muhammad Rizal Satria; Mubassiran Mubassiran (Universitas Ahmad Dahlan, 2026)
This study addresses a gap in halal marketing literature by examining halal awareness not only as a direct predictor but also as a moderator in the relationship between halal brand perceived quality and halal purchase intention among Generation Z consumers in Indonesia and Malaysia. A cross-sectional survey of 420 Muslim respondents aged 18–27 was conducted. Then, the primary data gathered were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that perceived quality of halal brands significantly enhances purchase intention, while halal awareness also plays an important direct role in shaping consumers’ behavioral intentions. More importantly, halal awareness strengthens the relationship between perceived quality and purchase intention, indicating that consumers with higher awareness are more responsive to halal quality signals. The results are consistent across both countries, suggesting that the underlying behavioral mechanism is stable despite differences in institutional contexts. This study contributes theoretically by integrating the Theory of Planned Behavior, signaling theory, and the Elaboration Likelihood Model, and by positioning halal awareness as a boundary condition in halal consumer behavior. Practically, the findings suggest that firms should complement improvements in halal product quality with targeted efforts to enhance consumer awareness, as this can strengthen the impact of quality signals and more effectively drive purchase intentions among Generation Z consumers.